The impact of customer perceived support on target-based customer citizenship behaviors: The mediating effects of brand reputation and satisfaction - Ahmed Hassaan Mohammed Ali; Jing Song; Min Zhang (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
Customers' voluntary behaviors (i.e., customer citizenship behaviors, CCBs) are of ever-increasing interest, given that they produce extraordinary value for service providers. Whether customer perceived support (CPS) from service providers leads to CCBs has remained largely understudied in service marketing literature. Moreover, the underlying mechanisms through which CPS can result in CCBs receives even less attention in previous studies. Thus, the purpose of this research is to examine the influence of CPS on target-based CCBs (customer- and firm-oriented CCBs), and the mediating roles of two important relational factors (customer-based brand reputation (CBR) and customer satisfaction (CS) in the relationship between CPS and CCBs in the context of after-sales service. Structural equation modeling using AMOS was employed to empirically test the hypotheses on survey data from 368 Chinese smartphone customers. The results showed that CPS positively influenced firm-oriented CCBs, while there was no direct link between CPS and customer-oriented CCBs. Furthermore, CBR and CS mediated the relationship between CPS and CCBs, respectively. This research contributed greater clarity and a better understanding of how CPS effectively boosts CBR and CS to encourage customers' voluntary behaviors desired by service providers.
Keywords: M31; 330; Customer perceived support; customer satisfaction; customer-based brand reputation; target-based customer citizenship behaviors; marketing